(untitled) (Polish Yearbook of International Law, 2017)
Wasteful spending of public funds, leading to the creation of “ghost airports”, is often described as a regulatory failure and a major defciency in European State aid control. It is pointed out that decisions to build or upgrade an airport are often ill-conceived, poorly implemented, and without economic justifcation. This raises the question whether European law, namely its State aid control system, contains inherent ﬂaws or whether the European Commission’s decision-making process can be improved by increasing reliance on objective economic reasoning under the existing legal framework. Tis article provides an analysis of the decision-making problems leading to failed aid eﬀorts; of the role of the economic approach in State aids; and of the standard of economic assessment required in State aid cases. The article concludes with de lege ferenda postulates.